Mucopolysaccharidosis and Adulthood: Genetics, Inheritance, and Reproductive Options - Wilson, Alison; Lavery, Christine; Stewart, Fiona; Thomas, Sophie; Cavell, Deborah; Brandon, Rebecca; Murphy, Elaine; Wilcox, Gisella; Talaulikar, Vikram (Journal of Child Science, 2018)
The mucopolysaccharide diseases are a group of heterogeneous, inherited conditions that are characterized by the deficiency of specific lysosomal enzymes. These lysosomal enzymes are responsible for the breakdown of glycosaminoglycans (GAGs), which are a key component of connective tissue. When lysosomal enzymes are deficient, the resultant build-up of GAGs impacts on cellular functioning. The resultant clinical manifestations are multisystemic, progressive, and life-limiting. Although each condition is characterized by its own constellation of symptoms; there is a great deal of heterogeneity and overlap in the clinical manifestations (both within and between mucopolysaccharidosis [MPS] subtypes). Increasing understanding of the genetic and biochemical basis of the MPS diseases has paved the way for a wave of exciting developments in their treatment and management. New treatments have changed the face of many of the MPS diseases; and as a result, management has moved beyond the pediatric clinic into the adult clinic. For the first time, individuals with MPS are living into adulthood with fewer limitations than the natural course of their disease would predict. It is essential that in this new age of MPS disease management, early diagnosis achieved and those at risk of having a child affected by one of these conditions are appropriately counseled in relation to their reproductive options. It is also important that individuals with MPS are counseled independently, at an appropriate age (or when they have capacity) about the basis of their disease and what this means for them. Here we discuss the diagnosis and inheritance of the MPS conditions; specifically focusing on genetic counseling requirements. We also discuss the outcomes of a research study, undertaken by the UK Mucopolysaccharide Disease Society, into the experiences of women with MPS who have had successful pregnancies.
Keywords: mucopolysaccharide; genetic counseling; inheritance; prenatal; preimplantation genetic diagnosis; pregnancy